PERANCANGAN DAN IMPLEMENTASI MULTIMEDIA INTERAKTIF DENGAN METODE EXPLORATORY TUTORIAL MATA PELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Jamaludin, Haris; Putra, Toni Wijanarko Adi; Sulartopo, Sulartopo; Hartono, Budi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
This study focuses on the design and implementation of interactive multimedia in Information and Communication Technology (ICT) subjects by applying the Exploratory Tutorial method. Along with technological advances and the need for more interesting learning methods, interactive multimedia is considered to be able to improve the understanding of ICT concepts more efficiently. The Exploratory Tutorial method was chosen because of its ability to provide an in-depth learning experience through an exploration approach and structured tutorials. This study includes design stages that include needs analysis, content design, and development of interactive multimedia applications, followed by an implementation stage that includes testing and evaluating the effectiveness of the application in improving student understanding. The findings of this study indicate that interactive multimedia built using the Exploratory Tutorial method can improve student engagement and understanding of ICT subjects, as well as provide useful feedback for the development of teaching materials in the future.